GSK3β Inhibition Prevents Macrophage Reprogramming by High-Dose Methotrexate - Israel Ríos; Baltasar López-Navarro; Mónica Torres-Torresano; Blanca Soler Palacios; Miriam Simón-Fuentes; Ángeles Domínguez-Soto; Ittai B. Muller; Gerrit Jansen; Ángel L. Corbí; Amaya Puig-Kröger (Karger Publishers, 2022)
Methotrexate (MTX) is an antifolate drug used as a chemotherapeutic agent for acute lymphoblastic leukemia, where MTX improves patients' prognosis. Macrophage reprogramming is being increasingly assessed as an antitumor therapeutic strategy. However, and although MTX limits the pathogenic action of macrophages in chronic inflammatory diseases, its effects on tumor-promoting macrophages have not been previously explored. We now report that MTX shapes the transcriptional and functional profile of M-CSF-dependent human macrophages, whose transcriptome is highly enriched in the gene signature that defines pathogenic tumor-associated macrophages ("large TAM"). Specifically, MTX prompted the acquisition of the gene signature of antitumoral "small TAM" and skewed macrophages toward an IL-6high IFNβ1high IL-10low phenotype upon subsequent stimulation. Mechanistically, the MTX-induced macrophage reprogramming effect correlated with a reduction of the M-CSF receptor CSF1R expression and function, as well as a diminished expression of MAF and MAFB transcription factors, primary determinants of pro-tumoral macrophages whose transcriptional activity is dependent on GSK3β. Indeed, the ability of MTX to transcriptionally reprogram macrophages toward an antitumoral phenotype was abrogated by inhibition of GSK3β. Globally, our results establish MTX as a macrophage reprogramming drug and indicate that its ability to modulate macrophage polarization may also underlie its therapeutic benefits. Since GSK3β inhibition abrogates the reprogramming action of MTX, our results suggest that the GSK3β-MAFB/MAF axis constitutes a target for the macrophage-centered antitumor strategies.